2015
DOI: 10.1111/anae.13218
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of hyperoxia during and after cardiac surgery

Abstract: SummaryDuring and after cardiac surgery with cardiopulmonary bypass, high concentrations of oxygen are routinely administered, with the intention of preventing cellular hypoxia. We systematically reviewed the literature addressing the effects of arterial hyperoxia. Extensive evidence from pre-clinical experiments and clinical studies in other patient groups suggests predominant harm, caused by oxidative stress, vasoconstriction, perfusion heterogeneity and myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 109 publications
1
47
0
1
Order By: Relevance
“…There is substantial consensus on the effects that longterm hyperoxia causes in healthy subjects: sympathetic activity decrease, as evaluated by muscular sympathetic nerve activity [4], by LFSP power [2] and by the LFRR/HFRR ratio [8]; augmented vagal activity as indicated by the increase of HFRR power [2,3,8], associated with HR reduction [2,3,4,8,9]; decreased stroke volume [2,9]; vasoconstriction due to a local effect [7,9], which has recently been considered the primary effect of hyperoxemia [1], eliciting an increase in peripheral resistance [2,3] and decreased blood flow to the limbs [4]. However, contradictory effects of hyperoxia have also been reported: reduction [6], no change [4] or increase [3] of AP; no change of BRS evaluated by alpha technique [7], and, when estimated by sequence analysis, increase [3] or reduction [2]; and either no change, decrease or increase of PV [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial consensus on the effects that longterm hyperoxia causes in healthy subjects: sympathetic activity decrease, as evaluated by muscular sympathetic nerve activity [4], by LFSP power [2] and by the LFRR/HFRR ratio [8]; augmented vagal activity as indicated by the increase of HFRR power [2,3,8], associated with HR reduction [2,3,4,8,9]; decreased stroke volume [2,9]; vasoconstriction due to a local effect [7,9], which has recently been considered the primary effect of hyperoxemia [1], eliciting an increase in peripheral resistance [2,3] and decreased blood flow to the limbs [4]. However, contradictory effects of hyperoxia have also been reported: reduction [6], no change [4] or increase [3] of AP; no change of BRS evaluated by alpha technique [7], and, when estimated by sequence analysis, increase [3] or reduction [2]; and either no change, decrease or increase of PV [5].…”
Section: Discussionmentioning
confidence: 99%
“…Because the effects of hyperoxemia are potentially harmful to the heart and vessels [1,3,9] and the risk of organic damage is proportional to the exposure time, in this study we limited 100%O2 breathing to a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal and clinical studies have shown that hyperoxia induces vasoconstriction in the brain, heart, and other tissues [2,7,8]. Hyperoxia can also exacerbate cardiovascular performance and induce cardiac hypertrophy and arrhythmias [9,10], for review see [11]. Therefore, medical uses of NBO or HBO treatments are controversial, and current guidelines recommend limiting exposure to excessively high oxygen concentrations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, medical uses of NBO or HBO treatments are controversial, and current guidelines recommend limiting exposure to excessively high oxygen concentrations [12]. Although molecular mechanisms of protective and adverse effects of hyperoxia are still not well understood, it is widely recognized that increased oxidative stress plays a principal role [2,11]. Increased formation of reactive oxygen (ROS) and nitrogen (RNS) species leads to changes in intracellular redox state and modulation of cell signaling pathways, resulting in alterations in gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation